HEALTH EDUCATION BRUSHING TEETH PROPERLY AND CORRECTLY FOR CHILDREN OF AL QURAN AL BAROKAH KINDERGARTEN PADANGSIDIMPUAN - harahap, Olivia Feby; Juliana; Zebua, Sherli Rahmadani; Nia puspita; Shella widari (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2025)
This community service activity aims to increase the understanding and knowledge of RA Quran Kindergarten students about clean and healthy living behavior (PHBS) and change students' behavior in living clean and healthy. The targets of the service were 25 students consisting of kindergarten A and kindergarten B class groups. The method used is the counseling method with three forms, namely lectures, interactive discussions, and practices. The practice of PHBS and consuming healthy food gives students the opportunity to learn directly through seeing, practicing and playing how to brush their teeth properly and correctly or bring healthy food from home (lunch) 4 healthy 5 perfect. The results of the service showed that there was an increase and change in students' knowledge, attitudes and actions in brushing their teeth properly and correctly and eating healthy food.